Do texto pelas mãos do escritor ao texto nas mãos do leitor: pensando a leitura e a escrita na biblioteca - Alessandra Bernardes Sexto (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2003)
What does reading and writing in the library signify? How do we constitute the reader-writer subject? What processes are involved when one is reading? And when one is writing? In which instances does the reader situate himself in the written text? In the already known set of discourses on reading/writing, I return to the voice of Mikhail Bakhtin who, in offering us another intonation, allows us to think the space of the library not only as a cultural territorialised space but, fundamentally, as a discursive space in which the most diverse voices confront each other. Taking the library in its textual- discursive dimension as our focus, I seek to construct a conception of acts of reading and writing in the processes of textual construction, based on the presuppositions of the theory of language of the same author, as well as in its forms of realisation as social-cultural practices in the diverse spheres of human activity.